Pre-synchronization grid-connection startup strategy for photovoltaic virtual synchronous generators based on sliding mode control - Shi, Chencheng; Tang, Yu; Hu, Mengjie; Wang, Zening; Xu, Zijun; Guo, Liang (Sustainable energy technologies and assessments, 2025)
Photovoltaic power generation is subject to random influences from the external environment, so the power quality of photovoltaic grid-connection systems cannot be guaranteed. To achieve smooth grid-connection photovoltaic load systems that can adapt to changes in the external environment, this paper proposes a new photovoltaic virtual synchronous generator (PV-VSG) pre-synchronization grid-connection control strategy. This strategy adapts to changes in the external environment by regressing and predicting the maximum output power of the photovoltaic array. The frequency modulation control method combined with power reserve is designed to enable the photovoltaic converter to independently support the grid voltage and frequency, and the flexibility of the grid-connection system to cope with external disturbances is improved through the variable step-size voltage tracking control of the photovoltaic array. This strategy does not require the use of energy storage batteries to stabilize the DC bus voltage but is implemented through a sliding mode controller, which successfully improves the robustness of the photovoltaic grid-connection system. In addition, this strategy also designs a slow start pre-synchronization algorithm for the PV-VSG, which successfully eliminates the power lag problem caused by the power imbalance of the bipolar photovoltaic grid-connection converter when connected to the power grid. •It is verified that environmental changes make photovoltaic grid-connection random.•A variable step-size voltage tracking strategy for photovoltaic array is proposed.•A frequency modulation control strategy combined with power reserve is designed.•A new virtual synchronous machine pre-synchronization algorithm is designed.•A sliding mode controller is used to stabilize the DC bus voltage.